Lecturers’ workload and research participation in MARA University of Technology Sarawak Branch Samarahan Campus / Constance Chin, Cindy Wee Song Yian and Khong Heng Yen - Chin, Constance; Wee, Cindy Song Yian; Khong, Heng Yen (2003)
This study aims to determine the workload of the lecturers and their research participation. It also attempts to investigate the existence of any relationship between research participation and lecturers’ workload as well as between research participation and the demographic characteristics of the respondents. In addition, the researchers hope to determine the factors that could hinder or promote research participation. This study was carried out in the form of a survey involving 113 lecturers of MARA University of Technology Sarawak Branch Samarahan Campus (UiTMCSKS). In addition eight UiTMCSKS lecturers who were actively involved in research were interviewed in order to gain an insight on how they managed their time so as to accommodate both teaching and research activities.